Analysis of Leg Muscle Power and Vo2max on The Performance of Karate Athletes - Azhar Faqihurrois Maulana; Alen Rismayadi; Sagitarius (Jurnal Pendidikan Jasmani (JPJ), 2026)
This study investigates the influence of leg muscle power and VO2Max on the performance of karate athletes. Leg muscle power is essential for explosive actions such as kicking and rapid positional shifts, while VO2Max reflects maximal aerobic capacity that supports endurance during matches. A quantitative descriptive method was employed through surveys and competition observations. The sample comprised six West Java Pelatda karate athletes who had competed at the national level. Instruments included the Multi-Stage Fitness Test (Beep Test) to measure VO2Max, a Force Plate to assess leg muscle power, and a match observation rubric based on the 2024 WKF regulations. Results showed that three athletes achieved VO2Max in the “excellent” category, while two athletes demonstrated leg muscle power in the “excellent” category. However, simple linear regression analysis revealed no significant effect of either VO2Max or leg muscle power on performance, with significance values greater than 0.05. The findings suggest that karate performance is not determined solely by physical conditions but is also shaped by strategy, technique, and mental readiness. Coaches are therefore encouraged to develop more comprehensive training programs that integrate physical, technical, and psychological components.